(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Wireless communications between mobile users is becoming very popular in today’s environment. This is due to technological advances in laptop computers and wireless communication devices, such as mobile phones, Laptops etc. In wireless networks, MANET is very popular in today. In this paper, we will evaluate the impact of Network Load and Node Mobility on the performance of Proactive, Reactive and Hybrid routing protocols of MANET on the basis of Packet delivery ratio. We will take CBR and TCP both types of traffics into consideration for performing the evaluation. We have used the NS-2 simulator for performing all the simulation work. Keywords: MANET, Packet Delivery Ratio (PDR), Network Load, Mobility, Traffic Pattern.